2003
DOI: 10.1002/mds.10639
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of sleep quality in patients with advanced Parkinson's disease treated with deep brain stimulation of the subthalamic nucleus

Abstract: Most Parkinson's patients complain about sleep problems. The subjective effect of deep brain stimulation (DBS) of the subthalamic nucleus (STN) on nocturnal disabilities and sleep quality was elucidated by the recently established Parkinson's disease sleep scale (PDSS). The DBS-treated group obtained significant improvement of motor function assessed by the Unified Parkinson's Disease Rating Scale. The mean total PDSS improved significantly after surgery whereas no change was found for the control group. Signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
60
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 11 publications
10
60
1
4
Order By: Relevance
“…Several authors reported an improvement in nocturnal sleep in PD patients who underwent deep brain stimulation. 146,147 The impact of deep brain stimulation on EDS, however, has not been systematically studied.…”
Section: Diagnosis Of Excessive Daytime Sleepiness In Parkin-son's DImentioning
confidence: 99%
“…Several authors reported an improvement in nocturnal sleep in PD patients who underwent deep brain stimulation. 146,147 The impact of deep brain stimulation on EDS, however, has not been systematically studied.…”
Section: Diagnosis Of Excessive Daytime Sleepiness In Parkin-son's DImentioning
confidence: 99%
“…In studies examining subjective sleep quality after subthalamic stimulation, overall sleep quality and total sleep time improved after STN-DBS. 3,4,5 To date, most studies including objective polysomnographic measures have been small case series, with different patient populations, study protocols, various assessment time points, and electrode settings: Arnulf and colleagues evaluated 10 insomniac PD patients 3 to 6 months after STN-DBS, and found stimulation to increase total sleep time and sleep efficiency. 6 Similar findings have been made by Monaca et al in 10 patients before STN-DBS and again after 3 months, 7 by Cicolin and colleagues in 5 patients before and 3 months after bilateral STN-DBS electrode implantation, 8 and by Merlino et al in 15 patients one week before and after microsubthalamotomy.…”
Section: Introductionmentioning
confidence: 99%
“…61 Another small study reported improvements in sleep architecture and quality, along with an increase in total sleep time (up to 47%) even in patients treated with subthalamic nuclei (STN) deep brain stimulation (DBS). 62,63 Moreover, an alleviation of "OFF" dystonia was registered after the microlesion effect produced by STN DBS surgical intervention. In this group of 30 patients, the morning of the third day following STN implantation, after at least a 12-hour withdrawal of dopaminergic treatment and before the programmable pulse generator was switched on, a significant clinical improvement was observed.…”
Section: Challenges and Solutionsmentioning
confidence: 95%